Clinical and Biochemical Characteristics of Male Workers in a Pesticide Production Factory in Guilan Province, Iran - Mir Saeed Attarchi; Fatemeh Nejatifar; Hamid Mohammadi Kojidi; Zahra Atrkar Roushan; Niloofar Faraji; Maryam Joshan; Fatemeh Rahattalab; Roholah Amini (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2022)
Background and Aim The high use of pesticides has increased the concern about its possible harm to individual and environment health. Chronic exposure to pesticides has serious effects on different body organs even before the onset of clinical symptoms. In this study, we aim to evaluate clinical and biochemical characteristics of male workers in a pesticide production factory in Guilan province, Iran. Methods & Materials This cross-sectional study was conducted on 99 male workers exposed to pesticide and 107 people without exposure who were employed in a pesticide production factory in Guilan and selected using a convenience sampling method in 2020. Their demographical data as well as clinical characteristics such as respiratory symptoms (cough, shortness of breath, etc.), neurological symptoms (fatigue, tremors, cramps, muscle weakness, etc.), psychological symptoms (sleep disorders, anxiety, etc.) and skin symptoms (redness, itching, etc.) were collected from the occupational health records of the workers. Finally, the biochemical parameters were compared between the two groups. Statistical analysis was performed in SPSS software, version 16. Ethical Considerations This study was approved by the Research Ethics committee of Guilan University of Medical Science, Rasht, Iran (Code: IR.GUMS.REC.1399.632). Informed consent was obtained from all participants in this study. Results The frequency of symptoms such as headache, itchy skin, cough, and sleep disorders was higher in the exposed group (P<0.05). Based on the biochemical findings, blood urea level, creatinine level, alkaline phosphatase, and fasting blood sugar level were significantly higher in the exposed group (P<0.05). Thrombocytosis was observed in 9.09% of exposed workers, which was higher in those with more than 11 years of work experience. Conclusion Chronic exposure to pesticide can cause thrombosis, changes in biochemical parameters, and clinical symptoms. It is recommended that biological monitoring should be conducted in exposed workers at a shorter interval.